People and forests : communities, institutions, and governance - Gibson, Clark C., 1961-; McKean, Margaret A.; Ostrom, Elinor (Politics, science, and the environment., 2000)
Unplanned deforestation, which is occurring at unsustainable rates in many parts of the world, can cause significant hardships for rural communities by destroying critical stocks of fuel, fodder, food, and building materials. It can also have profound regional and global consequences by contributing to biodiversity loss, erosion, floods, lowered water tables, and climate change. People and Forests explores the complex interactions between local communities and their forests. It focuses on the rules by which communities govern and manage their forest resources. As part of the International Forestry Resources and Institutions research program, each of the contributors employs the same systematic, comparative, and interdisciplinary methods to examine why some people use their forests sustainably while others do not. The case studies come from fieldwork in Bolivia, Ecuador, India, Nepal, and Uganda. People and Forests offers policymakers a sophisticated view of local forest management from which to develop policy options and offers biophysical and social scientists a better understanding of the linkages between residents, local institutions, and forests. ContributorsArun Agrawal, Abwoli Y. Banana, C. Dustin Becker, Clark C. Gibson, William Gombya-Ssembajjwe, Rosario Leon, Margaret A. McKean, Elinor Ostrom, Charles M. Schweik, George Varughese, Mary Beth Wertime